Psychometric properties and factor structure of the satisfaction with life scale in Ecuadorian university students - López-Guerra, Victor Manuel; Pucha-Loarte, Tatiana Isabel; Angelucci, Luisa T.; Torres-Carrión, Pablo V. (Frontiers in Psychology, 2025)
BackgroundThe Satisfaction with Life Scale (SWLS) measures the global cognitive judgment about one’s own life. Although it has been validated in different countries and populations, in the Ecuadorian context, it has not been validated for a university population.ObjectiveThe present study aimed to analyze the psychometric properties of the SWLS in a large sample of Ecuadorian college students.MethodsInstrumental-psychometric study with a sample of 4,524 participants from three Ecuadorian universities, with an average age of 22 (±3.15). The SWLS was evaluated in terms of its factor structure, factorial invariance, internal consistency and correlations with other measures related to mental health.ResultsThe SWLS factor structure optimally fits the single-factor model (X2/df = 3.79; CFI = 0.998; TLI = 0.996; SRMR = 0.023; RMSEA = 0.030). This model is invariant between men and women. The internal consistency of this instrument is acceptable according to the omega coefficient (ω = 0.84). The scores of this scale correlate, as expected, negatively with constructs such as depression and stress.ConclusionThe SWLS is a valid and reliable instrument to assess the personal perception of life satisfaction of Ecuadorian university students.